Arbeitnehmerschutzrechte bei Unternehmenskäufen – Einige rechtsvergleichende Anmerkungen Deutschland / Japan - Zierke, Jürgen; Schneemann, Jan (Zeitschrift für Japanisches Recht, 2004)
With sluggish economies in Japan and Germany during the last decade, companies in both countries have now been forced to respond to new competitive situations with corporate restructuring. This articles focuses on labor law–related issues regarding the business transfer (asset deal) and the sale of entire business units via the share deal, including remarks on special restructuring measures such as corporate divisions and mergers provided for by the governing laws in Germany and Japan. The articles shows that there are differences regarding employees’ rights in Japan and Germany, especially in the case of the business transfer. Japan has no statutory law that protects employees other than Civil Code Article 625, which provides that no employee shall be transferred without his consent (the transferring company also has the right to not transfer certain employees). In contrast to the Japanese rules, the German Civil Code § 613 a, allows employees to reject their transfer and prevents them from being excluded from the outset. Accordingly, the scope of employee protection, including union agreements, is broader in Germany. Both legal systems are similar regarding share deals because the change of entity ownership has basically no influence on the employees. However, the actual practice of corporate conglomerates (keiretsu) still prevails in Japan and makes the secondment practice from parent company to affiliated companies much more intensive than in Germany. This can result in the purchase of an entity without continuity of all employment relations because some staff (especially key persons) might legally belong to the parent company. The article furthermore shows that the two legal systems are not so different with regard to corporate division. This is the result of recent developments in the Japanese Commercial Law, under which employees are granted the right to object to a transfer and to be included in the list of employees to be transferred because of corporate division, rights that have already been in existence under the German Transformation Act for several years. Finally, the article analyzes how far changes in employment rules and termination rights could also affect employment relationships. It is noted that Japanese law is more flexible for employers than the German Civil Code.